Lumbal Flexibility in Songket Craftsmen in Palembang - Jesslyn Harapan; Indri Seta Septadina; Msy Rulan Adnindya (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Introduction. Flexibility in the human body is the range of abilities of certain joints or groups of joints in functional unity to move optimally,smoothly and pain-free. Lumbar flexibility is one of the most important factors that support daily human movement activities, such as walking and bending. Decreased lumbar flexibility occurs as human ages, this is also influenced by other related musculoskeletal complaints such as low back pain. Songket craftsmen generally have complaints of low back pain, due to the position and duration of work. This study was conducted to determine the relation of low back pain complaints with lumbar flexibility among weaving craftsmen in Palembang.Method. This research is an observational analytic study with cross sectional design using total sampling technique. Subjects were 31 weaving craftsmen in the city of Palembang. Lower back flexibility is measured using the Sit and Reach Test method. Data were analyzed using the Gamma Correlation test.Results. There is a significant moderate relation with a negative direction between lower back pain and lumbar flexibility in songket craftsmen (p = 0.022). The study shows that below normal lumbar flexibility scores were found in 11 people consisting of 9 male subjects (29.03%) and 8 subjects age 18-27 years old subjects (25.80%).Conclusion. There is significant relation between lower back pain in lumbar flexibility in Songket craftmen in Palembang.